Combating trafficking in Persons: A Handbook for Parliamentarians N° 16 - 2009 (2009)
The Handbook contains a compilation of international laws and good practices developed to combat human trafficking. It offers guidance on how national legislation can be brought in line with international standards by, for example, defining trafficking in persons and criminalizing all its forms. It outlines measures to prevent commission of the crime of trafficking in persons, to prosecute offenders and to protect victims. It also contains advice on how to report on this crime and how to enlist civil society in the cause.